2014
DOI: 10.1371/journal.pcbi.1003552
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Lever Arm Swing and Biased Brownian Motion in Actomyosin

Abstract: An important unresolved problem associated with actomyosin motors is the role of Brownian motion in the process of force generation. On the basis of structural observations of myosins and actins, the widely held lever-arm hypothesis has been proposed, in which proteins are assumed to show sequential structural changes among observed and hypothesized structures to exert mechanical force. An alternative hypothesis, the Brownian motion hypothesis, has been supported by single-molecule experiments and emphasizes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…We expect that the binding regulation mechanism using allosteric structural fluctuations applies also to other rail‐motor systems, such as other kinesins, actomyosin and the dynein‐MT system. In fact, a recent simulation studies of myosin II using a coarse‐grained model reported that structural fluctuation of loops regulates binding of the myosin to the actin filament. In the case of myosin V, the allosteric regulation of the affinity to actin filament through a large structural fluctuation of the helix H18 was also suggested by a molecular dynamics simulation .…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the binding regulation mechanism using allosteric structural fluctuations applies also to other rail‐motor systems, such as other kinesins, actomyosin and the dynein‐MT system. In fact, a recent simulation studies of myosin II using a coarse‐grained model reported that structural fluctuation of loops regulates binding of the myosin to the actin filament. In the case of myosin V, the allosteric regulation of the affinity to actin filament through a large structural fluctuation of the helix H18 was also suggested by a molecular dynamics simulation .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have shown great success in the studies of structural dynamics of actin filament due to the unprecedented spatial and temporal resolutions [23][24][25][26][27]. However, the molecular events involved in the filament growth typically occur at the time scales longer than millisecond, which are far beyond the capability of conventional all-atom MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to describe the driving force acting on myosin S1 along F‐actin on the basis of chemical thermodynamics, a mechanism with decreasing chemical potential of myosin S1 along F‐actin is required. The binding free energy between myosin S1 and F‐actin was calculated by molecular dynamics (MD) taking into account the electrostatic interactions and intermolecular interactions using the reproduced 3D coordinates of myosin S1 with/without ADP or ADP.Pi and F‐actin (Nie et al, ). This study showed a long distance driving force up to 11 nm after releasing ADP.…”
Section: Introductionmentioning
confidence: 99%